2016
DOI: 10.1016/j.ophtha.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Systemic Factors on Clinical Response to Ranibizumab for Diabetic Macular Edema

Abstract: There were no associations between systemic factors (baseline values or change from baseline) and mean change of BCVA at month 24. These results suggest that visual response to ranibizumab therapy in DME was not influenced by nonocular factors related to systemic management of diabetes in the RIDE and RISE studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 14 publications
4
36
1
2
Order By: Relevance
“…These results corroborate those of the post hoc analysis of the Rise and Ride study, in which no association was found between systemic factors and the mean change in BCVA over 2 years [6] . This suggests that the visual response to ranibizumab therapy for DME is not influenced by nonocular factors related to the systemic management of diabetes, even in a real-life setting [24] . In this study, we have shown that patients with a baseline BCVA lower than the first quartile threshold had the worst final BCVA, since these patients had a final BCVA of 43 letters (20/125) on average.…”
Section: Discussionmentioning
confidence: 91%
“…These results corroborate those of the post hoc analysis of the Rise and Ride study, in which no association was found between systemic factors and the mean change in BCVA over 2 years [6] . This suggests that the visual response to ranibizumab therapy for DME is not influenced by nonocular factors related to the systemic management of diabetes, even in a real-life setting [24] . In this study, we have shown that patients with a baseline BCVA lower than the first quartile threshold had the worst final BCVA, since these patients had a final BCVA of 43 letters (20/125) on average.…”
Section: Discussionmentioning
confidence: 91%
“…A recent post-hoc analysis of the RIDE and RISE trials evaluated the effects of systemic factors on vision changes from baseline in DME patients treated with RBZ [10] . The study revealed that the BCVA improvement with RBZ was not influenced by systemic factors, including diabetes medication history, serum glucose, glycosylated hemoglobin, blood pressure, body mass index, and renal function.…”
Section: © 2017 S Karger Ag Baselmentioning
confidence: 99%
“…In particular for DMO, the haemoglobin A1c and blood pressure in pivotal trials can be substantially different from ‘real-world’ patients,9 10 although a recent study suggests this may not affect outcomes of treatment 11. Electronic medical record (EMR) systems, if well-designed, offer more complete, prospective, real-time data collection as a by-product of routine care.…”
Section: Introductionmentioning
confidence: 99%